Dynamic analysis of a fractional-order SIRS model with time delay - Zhou, Xueyong; Wang, Mengya (Nonlinear Analysis: Modelling and Control, 2022)
Mathematical modeling plays a vital role in the epidemiology of infectious diseases. Policy makers can provide the effective interventions by the relevant results of the epidemic models. In this paper, we build a fractional-order SIRS epidemic model with time delay and logistic growth, and we discuss the dynamical behavior of the model, such as the local stability of the equilibria and the existence of Hopf bifurcation around the endemic equilibrium. We present the numerical simulations to verify the theoretical analysis.
Keywords: fractional calculus; epidemic model; stability; Hopf bifurcation; delay